My brother's husband. Volume 2 - Tagame, Gengoroh, 1964- (Pantheon Books, 2018)
As Mike continues his journey of discovery concerning Ryoji's past, Yaichi gradually comes to understand that being gay is just another way of being human. And that, in many ways, remains a radical concept in Japan even today. In the meantime, the bond between Mike and young Kana grows ever stronger, and yet he is going to have to return to Canada soon--a fact that fills them both with impending heartbreak. Concluding volume.